Task-based Language Teaching Implementation In Integrating EFL Students' Writing Skil - Eva Endah Nurwahyuni (Jurnal Inspirasi Pendidikan, 2021)
Lacks of students participation and also lacks of their basic understanding in constructing good sentences had become the major background of the researcher to conduct this study. This research article deals with a study conducted with students of Economic Faculty enrolled in EFL program. This study employed mixed methods analysis which analyzed the implementation of Task-based Language Teaching on EFL students and examined on how the strategy employed will impact on students’ writing skills. In addition, this research is also intended to find out the perception of instructor and students on the application of Task-based Language Teaching. The data in this research were collected through the process of observing, interviewing and analyzing students’ writing. By comparing the results, we can conclude that the students show improvement, either from the perspective of students’ participation or achievement. Moreover, the results also indicate that the majority of students and also instructor show positive perception towards the implementation of Task-based Language Teaching which was acknowledged with the growth of their study motivation and enjoyment. However, problems that deal with time availability and feedback are identified during the process, showing that a better preparation and further research are needed for better implementation in the future. Keywords: Task-based Language Teaching, Writing, EFL Classroom